New Biologics for the Treatment of Atopic Dermatitis: Analysis of Efficacy, Safety, and Paradoxical Atopic Dermatitis Acceleration. (30th May 2021) - Qi, Hong-jiao; Li, Lin-Feng
Abstract : Atopic dermatitis (AD) is a chronic, inflammatory skin disease with an eczematous rash and itching. Due to undesired adverse effects of traditional systemic treatment, there is still an unmet need for safe and effective long-term therapy for refractory AD. As our understanding of the pathogenesis underlying AD grows, novel treatments targeting specific molecules have been developed. Here, we discuss the efficacy and safety profiles of these drugs in recent clinical trials. Among their adverse effects, of particular note is AD acceleration. Although there is still debate about whether certain adverse reactions can be said to be paradoxical adverse events (PAEs), a wide range of PAEs have been reported during biological treatment for chronic immune-mediated diseases. Close surveillance of novel biologics is crucial to detect new undescribed paradoxical reactions and to shed light on the convoluted pathogenesis of AD.